HUBUNGAN ANTROPOMETRI LINGKARAN PERGELANGAN KAKI DENGAN KELINCAHAN PADA PEMAIN BOLA FUTSAL AMATIR USIA 13-16 TAHUN - Muhammad Khoirul Azis, (2023)
Anthropometric aspects greatly support the physical condition and skills of a technique where an athlete can demonstrate competency when carrying out movements. Anthropometry in futsal is a very important aspect, because the ankle is a focus area that is considered by the coach, because the ankle circle can affect the agility of the Futsal Player's feet. Purpose: This study was conducted to determine whether there is an anthropometric relationship between ankle circumference and agility in amateur futsal players at the Jakarta futsal club. Methods: This study used a cross-sectional correlation research design with a total sample of 66 futsal players. This study uses the figure of eight as an anthropometric measurement tool and the Agility T-Test to measure agility. Results: Obtained an average ankle size of 52.68cm and good agility category 29 (43.9%). Based on statistical test data for the anthropometric relationship between ankle circumference and agility in amateur futsal players at the Jakarta futsal club p=0.000 with r=-0,537. Conclusion: The conclusion drawn from this study is that there is a moderate relationship between anthropometry and agility.